Law No. 5 Of The Year 2021 On Postponing The Enforcement Of Law No. 186 Of The Year 2020 Amending Certain Provisions Of Law No. 114 Of The Year 1964, Organizing The Real Estate Registration And Notarization And Amending Certain Provisions Of The Income Tax Law Promulgated By Law No. 91 Of The Year 2005 = قانون رقم 5 لسنة 2021 بإرجاء العمل بالقانون رقم 186 لسنة 2020 بتعديل بعض أحكام القانون رقم 114 لسنة 1946 بتنظيم الشهر العقارى وبتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic